Segurança do trabalho: uma proposta de um framework integrador entre níveis de maturidade de cultura de segurança do trabalho, perfis de liderança e Análise Hierárquica de Processos (AHP) - Fukushigue, Kelly Aiko (2019)
Through work, the worker gets his livelihood and his family. In many cases, most part of the day is spent on work activities. This demonstrates the importance of having a safe and healthy environment for the individual to perform his or her function. However, there are situations where work is carried out in order to expose people to environmental risks. The high rate of accidents at work motivated studies on safety culture in companies. In view of this, this study aimed to propose a framework that integrates leadership style and the perception of stakeholders (formal leaders of the institution) to the evolution of the level of maturity of work safety culture. To achieve these objectives, qualitative research was used as a research method, through a study carried out on the maturity of the safety culture and leadership, using questionnaires as a tool for data collection, which were distributed to the workers and outsourced from a public educational institution. After analyzing the data by a specialist in occupational safety culture, criteria and subcriteria were defined aiming at the evolution from one level of safety culture maturity to another. This information was evaluated by two formal leaders of the institution and analyzed by the AHP (hierarchical process analysis) method. This method was used to allow aspects with a high degree of subjectivity to be analyzed and organized according to levels of importance. As a final result, it was observed that the combination of the methodologies carried out through an integrative framework between level of work safety maturity, leadership and its evolution evaluated by decision-makers and analyzed by the AHP method proved to be valid, since through this combination was able to classify the level of maturity of the security culture and the type of leadership of the institution, verifying that the institution studied presented a pathological level of safety culture maturity and a leadership of the transformational type. This result shows that even in an organization with transformational leaders, the safety culture's maturity may present incipient results, however, leadership style can be a possible impeller in changing the level of maturity of the security culture, with criteria being outlined and subcriteria for this evolution in the proposed method. Based on this result, suggestions were made for improvements in the safety culture maturity level according to the evaluation of the managers interviewed.